Full Coverage System Using High Altitude Platforms for East Coast Of Libya (Comprehensive Journal of Science, 2024)
In this paper, a High Altitude Platform system (HAPS) will be designed in order to provide full coverage area using five HAPS at east of Libya. Such system has the potential capability to serve a large number of users, either in dense urban areas or over a wide geographical area. They can be brought in temporarily for disaster relief or temporary coverage of entertainment events.The purpose of this study is to achieve the following objectives:i. Determining the location of the aircraft.ii. Computing the link budget for the uplink and downlink of the backhaul earth stations located at the edge of service and at10 Km far from the SPP of footprint.iii. Proposing one alternative backhaul earth terminal to improve the availability of the link. Computing the availability improvement to be achieved.